Financial reporting quality revisited: interactions between earnings management and the value relevance of accounting information. (30th November 2009) - Filip, Andrei; Di Vito, Jackie
The concept of financial reporting quality is not new. Earnings management, timely loss recognition and value relevance are often used in prior research as metrics of accounting quality. The objective of the present study is to analyse the interaction between these metrics. By using a sample of 576 Canadian listed firms, we predict that firms with less earnings management exhibit higher value relevance of accounting data. We provide evidence that earnings that are not manipulated (or do not need to be manipulated) are more informative than earnings that are.